Interactions between the Coxiella burnetii parasitophorous vacuole and the endoplasmic reticulum involve the host protein ORP1L. (15th July 2016) - Justis, Anna V.; Hansen, Bryan; Beare, Paul A.; King, Kourtney B.; Heinzen, Robert A.; Gilk, Stacey D.
Summary: Coxiella burnetii is a gram‐negative intracellular bacterium that forms a large, lysosome‐like parasitophorous vacuole (PV) essential for bacterial replication. Host membrane lipids are critical for the formation and maintenance of this intracellular niche, yet the mechanisms by which Coxiella manipulates host cell lipid metabolism, trafficking and signalling are unknown. Oxysterol‐binding protein‐related protein 1 long (ORP1L) is a mammalian lipid‐binding protein that plays a dual role in cholesterol‐dependent endocytic trafficking as well as interactions between endosomes and the endoplasmic reticulum (ER). We found that ORP1L localized to the Coxiella PV within 12 h of infection through a process requiring the Coxiella Dot/Icm Type 4B secretion system, which secretes effector proteins into the host cell cytoplasm where they manipulate trafficking and signalling pathways. The ORP1L N‐terminal ankyrin repeats were necessary and sufficient for PV localization, indicating that ORP1L binds a PV membrane protein. Strikingly, ORP1L simultaneously co‐localized with the PV and ER, and electron microscopy revealed membrane contact sites between the PV and ER membranes. In ORP1L‐depleted cells, PVs were significantly smaller than PVs from control cells. These data suggest that ORP1L is specifically recruited by the bacteria to the Coxiella PV, where it influences PV membrane dynamics and interactions with the ER.